Gambaran tingkat pengetahuan mahasiswa tahun pertama di Universitas PGRI Yogyakarta terhadap COVID-19 - Wahid, Rahmat A Hi; Karimatulhajj, Hanifah; Fitriani, Rosmauli Jerimia; Bertorio, Margala Juang (Pharmasipha : Pharmaceutical Journal of Islamic Pharmacy, 2023)
ABSTRACT The Corona Virus Disease 2019 (COVID-19) pandemic causes an increase in morbidity and mortality and affects the lives of global people. Knowledge of diseases, especially COVID-19, influences community compliance with control measures. Assessment of public knowledge, especially students during the pandemic crisis, is critical in attempting to overcome this outbreak. This study was conducted to assess the knowledge of first-year students at Universitas PGRI Yogyakarta towards COVID-19. Increased knowledge and awareness of students about COVID-19 is expected to break the chain of COVID-19 spread or social transmission. Preventive measures for the spread of COVID-19 can be carried out by carrying out handy hygiene, social distancing, wearing masks, and increasing the immune system and balanced nutrition. The research method used was a cross-sectional descriptive study. The sampling technique was non-random sampling with purposive sampling. Collecting data using an online questionnaire through social media networks consists of three main parts: socio-demographics, information sources, and knowledge of COVID-19. A total of 226 first-year students were included in the study; 71 (31.4%) were male, and 155 (68.6%) were female. The students mostly came from the non-health science field, which was 198 (87%) in amount, and aged 17-19 years were159 persons (70.4%). The results showed that the level of knowledge of students was classified as good (39.4%), sufficient (41.6%), and (19.0%) less. This research can conclude that the level of knowledge at Universitas PGRI Yogyakarta is sufficient, so it is necessary to increase understanding related to COVID-19 through continuous and intensive online education in the campus environment. Keywords: COVID-19, level of knowledge, first-year  pharmacist students, Universitas PGRI Yogyakarta   ABSTRAK Pandemik Corona Virus Disease 2019 (COVID-19) menyebabkan peningkatan morbiditas dan mortalitas serta mempengaruhi kehidupan masyarakat global. Kepatuhan masyarakat terhadap tindakan pengendalian dipengaruhi oleh pengetahuan terhadap penyakit khususnya COVID-19. Penilaian pengetahuan masyarakat khususnya mahasiswa selama krisis pandemik sangat penting dalam upaya untuk mengatasi wabah ini. Penelitian ini dilakukan untuk menilai pengetahuan mahasiswa tahun pertama di Universitas PGRI Yogyakarta terhadap COVID-19. Meningkatnya pengetahuan dan kesadaran mahasiswa akan COVID-19 diharapkan dapat memutus rantai penyebaran COVID-19 atau transmisi sosial. Tindakan preventif penyebaran COVID-19 bisa dilakukan dengan melakukan handy hygiene, social distancing, menggunakan masker, dan meningkatkan sistem imun serta gizi seimbang.  Metode penelitian yang digunakan adalah studi deskriptif dengan desain cross sectional. Teknik pengambilan sampel secara non random sampling dengan jenis purposive sampling. Pengambilan data menggunakan koesioner online melalui jejaring media sosial yang terdiri dari tiga bagian utama: sosio-demografi, sumber informasi, dan pengetahuan terhadap COVID-19. Sebanyak 226 mahasiswa tahun pertama dilibatkan dalam penelitian ini, 71 (31,4%) adalah laki-laki, dan 155 (68,6%) adalah perempuan. Latar belakang mahasiswa sebagian besar berasal dari bidang ilmu non Kesehatan berjumlah 198 (87%) dan berusia 17-19 tahun 159 (70,4%). Hasil penelitian menunjukkan tingkat pengetahuan mahasiswa yang tergolong baik (39,4%), cukup (41,6%), dan (19,0%) kurang.  Penelitian ini dapat disimpulkan bahwa tingkat pengetahuan mahasiswa tahun pertama di Universitas PGRI Yogyakarta tergolong cukup sehingga diperlukan peningkatan pemahaman terkait COVID-19 melalui edukasi secara online yang berkelanjutan dan intensif di lingkungan kampus. Kata Kunci: COVID-19, Tingkat Pengetahuan, Mahasiswa Tahun Pertama, Universitas PGRI Yogyakarta